Drosophila: A Model to Study the Pathogenesis of Parkinson’s Disease - Rahul; Siddique, Yasir H. (CNS & Neurological Disorders - Drug Targets, 2022)
Human Central Nervous System (CNS) is the complex part of the human body, which regulates multiple cellular and molecular events taking place simultaneously. Parkinsons Disease (PD) is the second most common neurodegenerative disease after Alzheimer’s disease (AD). The pathological hallmarks of PD are loss of dopaminergic neurons in the substantianigra (SN) pars compacta (SNpc) and accumulation of misfolded α-synuclein, in intra-cytoplasmic inclusions called Lewy bodies (LBs). So far, there is no cure for PD, due to the complexities of molecular mechanisms and events taking place during the pathogenesis of PD. Drosophila melanogaster is an appropriate model organism to unravel the pathogenicity not only behind PD but also other NDs. In this context as numerous biological functions are preserved between Drosophila and humans. Apart from sharing 75% of human disease-causing genes homolog in Drosophila, behavioral responses like memory-based tests, negative geotaxis, courtship and mating are also well studied. The genetic, as well as environmental factors, can be studied in Drosophila to understand the geneenvironment interactions behind the disease condition. Through genetic manipulation, mutant flies can be generated harboring human orthologs, which can prove to be an excellent model to understand the effect of the mutant protein on the pathogenicity of NDs.
Keywords: pathogenesis